2005
DOI: 10.1152/jn.00216.2005
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of Rhythmic Motoneuron Activity During Fictive Locomotion and Scratch Provide Clues to the Organization of the Mammalian Central Pattern Generator

Abstract: We examined the features of spontaneous deletions of bursts of motoneuron activity that can occur within otherwise rhythmic alternating flexor and extensor activity during fictive locomotion and scratch in adult decerebrate cats. Deletions of activity were observed both in hindlimb flexor and extensor motoneuron pools during brain stem-stimulation-evoked fictive locomotion but only in extensors during fictive scratch. Paired intracellular motoneuron recordings showed that deletions reduced the depolarization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
232
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 206 publications
(254 citation statements)
references
References 30 publications
21
232
1
Order By: Relevance
“…A similar conclusion about separation of rhythm and motoneuron activation duties arose from intracellular studies of deletions of scratch reflex activity in the turtle (Robertson and Stein, 1988). Our observations on deletions and on the ability of sensory stimulation to alter phase switching within the ongoing step cycle without changing the phase of the post stimulation rhythm (e.g., Guertin et al, 1995;Perreault et al, 1995;Stecina et al, 2005) led to the proposal for a two-level CPG (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a). It was recently suggested that a single-level CPG could produce non-resetting deletions if there were a powerful control mechanism that could regulate synaptic transmission between excitatory CPG interneurons and motoneurons (Kiehn, 2006).…”
supporting
confidence: 57%
See 1 more Smart Citation
“…A similar conclusion about separation of rhythm and motoneuron activation duties arose from intracellular studies of deletions of scratch reflex activity in the turtle (Robertson and Stein, 1988). Our observations on deletions and on the ability of sensory stimulation to alter phase switching within the ongoing step cycle without changing the phase of the post stimulation rhythm (e.g., Guertin et al, 1995;Perreault et al, 1995;Stecina et al, 2005) led to the proposal for a two-level CPG (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a). It was recently suggested that a single-level CPG could produce non-resetting deletions if there were a powerful control mechanism that could regulate synaptic transmission between excitatory CPG interneurons and motoneurons (Kiehn, 2006).…”
supporting
confidence: 57%
“…1F) all of the last order interneurons exciting motoneurons receive sensory input. Accordingly, this might be considered a three-level CPG organization.Our studies had shown that non-resetting deletions were quite common during fictive locomotion and scratch in the decerebrate cat (Lafreniere-Roula and McCrea, 2005). The simple explanation was that some circuitry separate from that involved in rhythm generation was responsible for the rhythmic depolarization and hyperpolarization of motoneurons.…”
mentioning
confidence: 84%
“…2; Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a,b andRybak, 2008;see Kiehn, 2006 for additional discussion on this point). Although there is much evidence that the last-order, pattern-forming circuitry is organised in half-centre modules (see above), there is little evidence that the rhythm-generating layer follows suit.…”
Section: Pattern Formation and Rhythm-generating Modulesmentioning
confidence: 99%
“…While McCrea and colleagues present some compelling evidence in support of a two-layer model, their evidence that the rhythm-generating layer is organised as half-centres is much less convincing. These investigators rely on spontaneous (Lafreniere-Roula and McCrea, 2005;Rybak et al, 2006a) or evoked (Rybak et al, 2006b) "deletions" of activity in single motor nerves that either are ("resetting" deletions) or are not ("non-resetting" deletions) associated with disruptions of rhythm. They reason that since these non-resetting deletions can be seen in either flexor or extensor muscle nerves, the rhythm-generating layer must excite both the flexor and extensor pattern formation half-centres.…”
Section: Pattern Formation and Rhythm-generating Modulesmentioning
confidence: 99%
See 1 more Smart Citation